1988
DOI: 10.1111/j.1365-2559.1988.tb01941.x
|View full text |Cite
|
Sign up to set email alerts
|

Granular cell tumours revisited. An immunohistological and ultrastructural study

Abstract: Twenty-five granular cell tumours were stained with a panel of antibodies to histiocytic, muscle, neural, neural crest, epithelial and endothelial markers. Electron microscopy was also performed in six cases. Twenty-four of the cases were similar morphologically and immunocytochemically. One case with features of an endothelial origin is described. The present study strongly supports the viewpoint that granular cell tumours are a distinct entity rather than being the common appearance of a group of lesions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
6

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(58 citation statements)
references
References 27 publications
2
50
0
6
Order By: Relevance
“…However, several other investigators have reported negative staining for GFAP in the tumor, which constitutes evidence against a pituicyte origin [9,15,17,21]. A third hypothesis, which is endorsed by some authors, including us, believes that, due to the variable immunoreactivity, these tumors are biologically heterogeneous in spite of histological homogeneity [4,26].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, several other investigators have reported negative staining for GFAP in the tumor, which constitutes evidence against a pituicyte origin [9,15,17,21]. A third hypothesis, which is endorsed by some authors, including us, believes that, due to the variable immunoreactivity, these tumors are biologically heterogeneous in spite of histological homogeneity [4,26].…”
Section: Discussionmentioning
confidence: 74%
“…These tumors were initially believed to be an aberrant growth of embryological tissue and were called "choristomas" [11]. Later, the term "granular myoblastoma" was suggested because of the similarity to the GCTs of the tongue originally considered to be derived from embryonic muscle cells [4,12,13]. There is, however, no evidence that these neurohypophysial tumors originate from muscle cells [14], due to their negativity for immunoperoxidase staining for desmin and smooth muscle actin.…”
Section: Discussionmentioning
confidence: 99%
“…[34] Some authors support a peripheral nerve-related cells origin for the majority of GCTs based on the finding of cytoplasmic granules with numerous membrane-bound vacuoles (which contain myelin-like tubules) and indicating some relationships with pre-existent axons. [30,35,36] It is also to be remembered that granular cell populations have been described in some nonneural neoplasms of the oral cavity such as ameloblastoma, ameloblastic fibroma, odontogenic fibroma, odontogenic cysts, and oral lichen planus. [37,38] Although, these tumors are S100-negative, in contrast to the classic GCT.…”
Section: Kaustuv Das Biswas Et Al Present Case 12years-tongue 2014mentioning
confidence: 99%
“…The granular cell tumors show immunoreactivity for S-100 protein (Fig. 3), vimentin, neuron-specific enolase (NSE), CD68 and CD57 [6] [7]. We used the following monoclonal primary antibodies: anti-CD68 (PG-M1, prediluited; DAKO, Carpinteria, CA, USA), anti-CD57 (QBEND-10, DAKO, Carpinteria, CA, USA) and S-100 protein (polyclonal, prediluited, Dako).…”
Section: Case Presentationmentioning
confidence: 99%